The era of great disasters Japan and its three major earthquakes - Iokibe, Makoto 1943-; Gonzalez, Tony
"The Era of Great Disasters examines modern disaster response in Japan, from the changing earthquake preparations and regulations, to immediate emergency procedures from the national, prefectural, and city levels, and finally the evolving efforts of rebuilding and preparing for the next great disaster in the hopes of minimizing their tragic effects. This book focuses on three major earthquakes from Japan's modern history. The first is the 1923 Great Kanto? Earthquake, which struck the capital region. The second is the 1995 Great Hanshin-Awaji Earthquake, affecting the area between Kobe and Osaka. The third is the 2011 Great East Japan Earthquake, the magnitude 9.0 quake that struck off the Pacific coast of the To?hoku region, causing a devastating tsunami and the nuclear accident. While the events of (and around) each of these earthquakes are unique, Professor Iokibe brings his deep expertise and personal experience to each disaster, unveiling not only the disasters themselves but the humanity underneath. In each case, he gives attention and gratitude to those who labored to save lives and restore the communities affected, from the individuals on the scene to government officials and military personnel and emergency responders, in hope that we might learn from the past and move forward with greater wisdom, knowledge, and common purpose"
"Originally published in Japan by Mainichi Shimbun Publishing Inc., in 2016."
Includes bibliographical references and index.
Keywords: Emergency management -- Japan; Tohoku Earthquake and Tsunami, Japan, 2011.; Kobe Earthquake, Japan, 1995.; Kanto Earthquake, Japan, 1923.